Situational Crisis Communication Theory Analysis on PT Kereta Api Indonesia's Crisis Response to the Argo Bromo Anggrek Train Incident in 2026 - Sausan Nur Shabrina; Fitria Ayuningtyas; Nurannafi Farni Syam Maella (International Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the crisis communication strategy implemented by PT Kereta Api Indonesia (KAI) in handling the 2026 Argo Bromo Anggrek train incident using the Situational Crisis Communication Theory (SCCT) framework. This research employed a qualitative descriptive approach with document analysis as the primary data collection technique. The data were obtained from official statements, press releases, company publications, and relevant news reports related to the crisis response undertaken by PT KAI. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings indicate that PT KAI implemented three major crisis communication strategies, namely instructing information, adjusting information, and rebuild strategy. Instructing information was reflected in the dissemination of information regarding the chronology of the incident, evacuation processes, and operational updates. Adjusting information was demonstrated through expressions of empathy and condolences toward victims and their families. Meanwhile, rebuild strategy emerged as the dominant approach through victim assistance, safety evaluation commitments, and efforts to restore public trust. The study concludes that the implementation of crisis communication strategies aligned with SCCT principles contributes to effective crisis management and organizational reputation recovery. This research provides theoretical contributions to crisis communication studies and practical recommendations for public transportation organizations in responding to crisis situations.